2016
DOI: 10.1007/s00238-016-1252-0
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life improves early after gender reassignment surgery in transgender women

Abstract: BackgroundFew studies have examined the long-term quality of life (QoL) of individuals with gender dysphoria, or how it is affected by treatment. Our aim was to examine the QoL of transgender women undergoing gender reassignment surgery (GRS).MethodsWe performed a prospective cohort study on 190 patients undergoing male-to-female GRS at Karolinska University Hospital between 2003 and 2015. We used the Swedish version of the Short Form-36 Health Survey (SF-36), which measures QoL across eight domains. The quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 19 publications
3
83
0
6
Order By: Relevance
“…The earliest articles included within this review were published in 2006 [ 17 , 87 ] whilst the most recent papers were published in 2017 [ 31 , 32 , 55 , 57 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest articles included within this review were published in 2006 [ 17 , 87 ] whilst the most recent papers were published in 2017 [ 31 , 32 , 55 , 57 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measure was validated in a wide variety of clinical and non-clinical populations, and it displayed an internal consistency value of .88 when used with Transgender populations [ 63 ]. This tool was employed by six studies reported on within this review [ 43 , 54 , 55 , 64 66 ]. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Access to gender-affirming care is associated with improvements in psychological health [12][13][14][15][16] and quality of life, 15,[17][18][19] reduced HIV incidence, 16,20 decreased viral load, 21 decreased substance use, 22 and increased engagement in preventive health services. 23 However, trans people face numerous and extraordinary barriers in obtaining gender-affirming care.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most research on the surgical experiences of gender diverse patients involved exclusively adult 6 11 and/or transfeminine 7 , 8 , 10 , 11 samples. Preliminary research with transmasculine patients has demonstrated that gender-affirming surgery is associated with better quality of life, 12 , 13 including decreased chest-related dysphoria after top surgery 13 , 14 and better perceived gender congruence after bottom surgery.…”
Section: Introductionmentioning
confidence: 99%